THE IMPACT OF ALTRUISM MESSAGES IN GREEN PRODUCT ADVERTISING ON CONSUMER ATTITUDE: A SURVEY TO GEN Z - Tania, Adialita; Miryam Ariadne, Sigarlaki; Sarah Febrina, Yolanda (INTI International University, 2023)
Companies in Indonesia have started doing green marketing, creating eco-friendly products, and exploding advertising in the media which is ecologically sound marketing. However, ads oriented to moral values (value-oriented) are the least likeable. It has caused consumers to become confused, doubtful, and apathetic about the integrity of green marketing activities. Therefore, communicating the advantages of certain brands for the environment and society is very important in running a good business, mainly if the ad is aimed at generation Z, who adhere to green values and sustainability, where these values can affect their attitude towards a brand. This study aims to provide information about the level of altruism in generation Z, along with measuring their attitudes towards advertisements containing altruistic messages so that companies can design appropriate communication strategies to persuade more consumers and customers to buy environmentally friendly products. The method used is the descriptive-associative method. Data collection techniques will be carried out using a quantitative approach with a survey design and a qualitative approach with a lab experiment design. The survey was used to identify samples with altruistic and non-altruistic characteristics. At the same time, this study used the experimental method to determine the impact of advertising with altruistic and non-altruistic messages on both groups of respondents. This study's determination of the sample uses a non-probability sampling totaling 181 Z generation respondents. Advertisements containing altruism messages, especially those containing environmentally sound messages, can positively impact the attitudes of Z generation respondents with both moderate altruistic and non-altruistic characteristics. However, although some of them like the advertising stimulus message in the altruism category, most do not yet have an interest in buying it.